History of Muhammadiyah Politics as a Neutral Organization - Siagian, Khairul Azmi; Nurhakim, Moh. (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aimed to discover the history of Muhammadiyah politics, including Muhammadiyah's political ideology, the pattern of Muhammadiyah relations with political parties, Muhammadiyah views on democracy, and Muhammadiyah's participation in the national political constellation since the founding of the MIAI. The study used historical method with the stages of (1) choosing a topic, (2) gathering sources, (3) verifying, (4) interpreting, and (5) writing. Further, data collection techniques in this study used library techniques. This study showed that Muhammadiyah uses political strategies, such as the Khittah Ujung Pandang 1971 and Khittah Denpasar 2002, as political guidelines. In its history, Muhammadiyah has three relationship patterns with political parties: direct relationship patterns, indirect relationship patterns, and neutral relationship patterns. Furthermore, Muhammadiyah is not anti-politics; Muhammadiyah even supports democracy based on ethics. Muhammadiyah's involvement in politics has started since it participated in MIAI, PII, Masyumi, and Parmusi.